Warfare in Ancient India : Organisational and Operational Dimensions - Thapliyal, Uma Prasad, (Brill | Manohar Publishers & Distributors, 2024)
The military history of ancient India has not attracted the attention of scholars in sufficient measure. Naturally, not many good books are available on the subject. Consequently, Indians know little about the military system followed by their ancestors. A serious effort is, therefore, needed to analyse and interpret the source material which lies scattered in ancient Indian literature, including scriptures and archaeological remains including inscriptions and coins, to produce a tangible thesis on the subject. This book is an humble effort in that direction. The book tries to present a complete picture of Indian military system from the earliest times. The topics covered include military organization, conduct of war, strategical and tactical concepts, weapons and armour, fortification, education and training and ceremonials. Some ancillary aspects related to war such as defence production, logistics, intelligence, medical services, engineering, signals, etc., have also been covered. The study is based on historical data. The myths and legends if not supported by historical evidence has been ignored. Each chapter is a complete study and is intended to generate a new thinking on the subject among lay readers and scholars alike.